Leptomeningeal Gadolinium Enhancement in Autoimmune GFAP Astrocytopathy. (26th April 2022) - Azzolini, Federica; Farina, Antonio; Gastaldi, Matteo; Barilaro, Alessandro; Scotti, Valentina; Falchetti, Giorgia; Fainardi, Enrico; Moretti, Marco; Massacesi, Luca
Abstract : A 46-year-old woman presented with urinary retention, headache, tremor, ataxia, mental slowness, and tetra-hyperreflexia following urinary infection. MRI showed signs of encephalomyelitis with diffuse postcontrast 3D fluid-attenuated inversion recovery leptomeningeal enhancement, a common finding in several neuroinflammatory conditions 1 (Figures 1 and 2). An extensive diagnostic workup (serum and CSF neurotropic viruses, Borrelia burgdorferi, Treponema pallidum, serum anti–myelin oligodendrocyte glycoprotein and anti–aquaporin-4 antibodies, antinuclear antibodies, extractable nuclear antigen, antineutrophil cytoplasmic antibodies, angiotensin-converting enzyme and α-chitotriosidase levels, quantiferon, total body CT scan) was unrevealing. CSF analysis disclosed lymphocytic pleocytosis (204 leukocytes/μL), high protein levels (123 mg/dL), CSF-restricted oligoclonal bands, and anti–glial fibrillary acidic protein (GFAP) antibodies (cell-based assay), leading to the diagnosis of autoimmune GFAP astrocytopathy. 2 After receiving IV methylprednisolone, the patient improved substantially.